Determination of Adjacent Visual Buffer Zones for the Temple Town of Chiang Mai City - Janjira Sukwai; Nattasit Srinurak (Heritage)
Buffer zone delineation often extends from the outermost edge of a site boundary for a specific distance. This study proposes a novel approach to determining the visual buffer for the temple town of Chiang Mai city. Adjacent Visual Buffer (AVB) was determined for the temples and their approaching routes using a GIS-based visibility method based on the viewing feature’s visual coverage and the observer’s visual range. The findings revealed that the total viewshed/visual range characterized the visibility of the temples in relation to the viewing feature’s height, resulting in AVB radii of varying sizes. The highest AVB radius of more than 200 m was found for temples situated in the city’s core, followed by those located on the city’s main streets and in isolated areas. The approaching route buffer was determined as a radius of 25 m from the road’s center. Interestingly, the density map results were consistent with the temple buffer results, indicating that the main roads of Chiang Mai’s historic area are highly used as an approaching route for temples. Combining the visual buffers of both temples and their approaching routes can aid in determining the level of control or guideline requirements in specific roads and areas.